Epilepsy surgery program in a resource‐limited setting in Vietnam: A multicentered collaborative model. Issue 4 (5th October 2022) - Le, Viet‐Thang; Thuy Le, Minh‐An; Nguyen, Duc Hue; Tang, Loc Ngoc Phuong; Pham, Tuan Anh; Nguyen, Anh Minh; Nguyen, Minh Kien; Van Ngo, Tan; Tran, Thanh Trung; Van Le, Tuan; Jallon, Pierre; Lim, Kheng‐Seang
Abstract: Objective: Although epilepsy surgery is more effective than medical therapy for drug‐resistant patients, it is underutilized in both high‐income and low‐ and middle‐income countries. In light of our efforts to establish an epilepsy surgery program in a resource‐limited setting, this study aimed to determine the outcome of the epilepsy surgery program in Ho Chi Minh City (HCMC), Vietnam. Methods: In 2018, we developed the HCMC epilepsy core multidisciplinary team with members from various hospitals and centers. The team typically included neurologists, neurosurgeons, neuropsychologists, psychiatrists, and nursing specialists. Presurgical evaluations were performed for patients with drug‐resistant epilepsy, fulfilling the ILAE criteria, with an epileptogenic lesion (mesial temporal sclerosis, low‐grade gliomas, or focal cortical dysplasia). All epilepsy surgeries were performed in two epilepsy surgery centers in HCMC between 2018 and 2021. The patients were followed up for at least 12 months. Results: Fifty‐two patients with drug‐resistant epilepsy underwent presurgical evaluation, of which 35 underwent surgery. Among the 52 patients, 20 (38.5%) underwent surgery after showing concordance among the results of standard presurgical assessments such as semiology, scalp interictal or ictal electroencephalography, and brain imaging. Among the 26 people with epilepsy who required more advanced evaluations, 15 underwent surgery with intraoperative electrocorticography to delineate the optimal resection borders. The outcomes of Engel Class I and Class II were achieved in 29/35 (82.8%) and 6/35 (17.2%) patients, respectively. Significance: The epilepsy surgery program with a multicentered collaborative model in a resource‐limited setting showed favorable outcomes in HCMC, Vietnam.